PENGARUH E-GOVERNMENT DAN BUDAYA ORGANISASI TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) PADA SEKRETARIAT DAERAH KABUPATEN JEMBRANA - Sandrayani, Ni Made Dwi Frida; Purwanto, Agus Joko; Rulinawaty, Rulinawaty (Journal of Industrial Engineering & Management Research, 2022)
Advances in information technology, the values and norms adopted by the State Civil Apparatus (ASN), especially in the Regional Secretariat of Jembrana Regency, are closely related to their performance in implementing the governance. This study is intended to determine whether there is an influence between e-government on the performance of the State Civil Apparatus (ASN), organizational culture with the performance of the State Civil Apparatus (ASN) and whether e-government and organizational culture have a simultaneous effect on the performance of the State Civil Apparatus (ASN) at the Regional Secretariat of Jembrana Regency. This research is a quantitative study with the sampling method used is the saturated sample method, i.e the entire population is used as research subjects which is  totaling 164 ASN in the Regional Secretariat of Jembrana Regency. The data analysis method uses Classical Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Analysis, t Test and F Test. From the results of the t-test, it can be concluded that e-government (X1) and organizational culture (X2) have a positive and significant effect on the performance of ASN (Y). Based on the results of the F test, it can be concluded that the variables of e-government (X1) and organizational culture (X2) have a positive and significant effect on the performance of ASN (Y) in the Regional Secretariat of Jembrana Regency.